Enhancing Repository Application UI/UX through Design Thinking Methodology - Ramadhan, Ikhwan Farhan; Adam Sekti Aji (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This research discusses the application of Design Thinking methods in redesigning the user interface (UI) and user experience (UX) of an academic repository website. With the growing need for user-centered design, this research focuses on how a Design Thinking approach can be used to improve the usability and visual appeal of a repository website. The method includes five main stages: Empathize, Define, Ideate, Prototype, and Test, which were applied to deeply understand the user experience through interviews and observations. Data was collected using the System Usability Scale (SUS) and the results showed a low score, indicating major problems in the aspects of navigation, accessibility, and monotonous visual design. The results of this study showed significant improvements in website functionality and user satisfaction, achieving an average SUS score of 93.58, classified as “Excellent” (Grade A). The redesign process yielded a modern and minimalist interface that enables users to access features with ease, enhancing information retrieval and overall engagement. This research underscores the critical role of design thinking in creating accessible, aesthetically pleasing, and user-friendly interfaces that align with user needs. By prioritizing empathy and iterative development, the study highlights the potential of design thinking to revolutionize UI/UX design, ensuring impactful and satisfying digital experiences.